2022
DOI: 10.1177/21925682221116823
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for 30-day Unplanned Readmission following Surgery for Lumbar Degenerative Diseases: A Systematic Review

Abstract: Study design Systematic review. Objectives Surgical procedures for lumbar degenerative diseases (LDD), which have emerged in the 21-century, are commonly practiced worldwide. Regarding financial burdens and health costs, readmissions within 30days following surgery are inconvenient. We performed a systematic review to integrate real-world evidence and report the current risk factors associated with 30-day readmission following surgery for LDD. Methods The Cochrane Library, Embase, and Medline electronic databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 79 publications
(393 reference statements)
0
3
0
Order By: Relevance
“…[ 11 , 17 ] Regarding postoperative outcomes, readmission following surgery is another event that is of concern to surgeons, as it presents a significant financial burden. [ 4 ] Rosenberg et al [ 16 ] reported that patients who were initially admitted on weekends and who underwent elective thoracolumbar spinal fusion surgery were more likely to experience hospital readmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 11 , 17 ] Regarding postoperative outcomes, readmission following surgery is another event that is of concern to surgeons, as it presents a significant financial burden. [ 4 ] Rosenberg et al [ 16 ] reported that patients who were initially admitted on weekends and who underwent elective thoracolumbar spinal fusion surgery were more likely to experience hospital readmission.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] With respect to patient satisfaction, emerging studies have focused on postoperative outcomes, health costs, and re-admission rates. [3][4][5][6] In addition to the impact of different surgical procedures and the general condition of patients, interestingly, some studies have investigated whether there is a weekend effect that will have an impact on postoperative outcomes. [7,8] Lamn first described the concept of a weekend effect and poorer outcomes for patients admitted to hospitals on weekends in 1973.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Several articles in the literature have analyzed large North American databases, 1,2,10,13-29 data from North American single centers, 5-7,9,30-34 and systematic reviews. 3,4,35 Four works from single centers outside the United States were found: one Finnish, 36 one Romanian, 37 one Indian, 38 and one Korean. 8 A Latin American multicenter study was published analyzing readmissions after surgery for adult deformity.…”
Section: Discussionmentioning
confidence: 99%